Cognitive, affective attributes and conative, behavioural responses in retail corporate branding - Vinhas da Silva, Rui; Alwi, S. F. S. (Journal of Product and Brand Management, 2006)
Purpose - The main aim of the present study is to empirically test a model of antecedents and consequences of corporate brand image (CBI) in two book retailers, one selling exclusively online, and the other selling exclusively offline in a British context. Design/methodology/ap proach - The study employed a survey to investigate the relationships of the antecedents and consequences of the CBI. The sample (n=511) comprised experienced customers of these two bookstores (visitors and shoppers of the site or bookstore). The antecedents of CBI which were the functional aspects of brand attributes (such as ease of use, secured web site, interactivity/building relationship, customer care and reliability) were combined with the CBI itself (emotional aspects of the corporate brand or personality traits of the company) and, further, the consequences of these emotional aspects such as customer satisfaction and loyalty were tested using a cross-sectional study. Findings - Using two separate structural equation models, the study found an empirical relationship between the brand attributes and the corporate brand image (the emotional values). This relationship in turn influences the customer's responses (loyalty). Research limitations/implications - By combining two methodological approaches of brand image evaluation: cognition (assessed through tangible and intangible brand attributes) and affect/emotion (assessed through brand personality scale) this study intends to add to the current understanding of consumer brand knowledge, in particular when the consumer is assessing a company's brand image (the CBI) and also learn how important the effect of cognitive attributes (such as brand attributes of a store and web site) is in explaining the subsequent CBI, and the integration effect on consumer responses such as brand loyalty. Do cognitive evaluations drive conative, behavioural actions in retail buying decision making? Are cognitive evaluations directly related with satisfaction with the retailer and consumer loyalty? Practical implications - Explicitly, the present study offers practitioners a research framework, aimed at guiding them as to how they could understand their defined or desired brand values (the corporate core values) among their consumers. Originality/value - In general, the present study adds to the existing literature in cognitive and affective attributes in consumer judgement and corresponding conative or behavioural attitudes in branding and reputation management. It brings together the concept of functional brand attributes, emotional brand attributes (the CBI), and the dependent variables such as customer satisfaction and loyalty in a unique context (internet), and compares this with the bricks and mortar context.